KEBIJAKAN ALOKASI DANA DESA (ADD) DI DESA PENTEK - Sukardy E.21109111 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
Problems of this study are the lack of adherence in the implement the operational instructions, such as not effective in making letters accountability, unclear use of funds allocation funded rural village allocation. This study aims to describe the implementation of the Program Allocation Fund Village in the Village District Pentek Sadaniang Pontianak regency with a qualitative approach. The research found that the Village Fund Allocation Policy Implementation in the Village District Pentek Sadaniang shows that the communication process obtained the following information: 1) the existence of socialization by District Team, 2) achievement information from policy makers to policy implementers in full swing, 3) there is consistency in the achievement of a message / command policy means there are no conflicting orders. While the block in this communication is dissemination to the public on policies ADD does not exist, so the lack of public understanding about ADD, this will result in difficulty invites public participation in the implementation and in monitoring the activities of ADD. Responding to phenomena of communication in the socialization of policy implementation ADD should be given to the public so as to understand the policies of ADD, people will also be easier to be invited to participate in the implementation of ADD, to help preserve the results of the implementation of ADD ADD oversee and participate in accordance with the provisions of the existingKeyword: Financial Policy, Fund Allocation of Village Depelompemnt, Distribution of Village Fund.